SCM Practice at ABC Paper Industry - Vivek, Dr. N.; Prabhakaran, B. (Journal of Contemporary Research in Management (JCRM), 2013)
The importance of this research is underpinned by the fact that the paper industry which uses waste paper as raw material has no well defined supply chain and there is a long felt need to understand how the supply chain works. The industries that use waste paper as raw material are mostly SME’s(Small Medium Enterprise) and due to this reason the companies do not develop a suitable supply chain model instead they benchmark a regional leader and function accordingly. Due to non availability of a suitable supply chain model, forecasting becomes difficult and the company has to face uncertainties in raw material procurement, production scheduling, order delivery, material requirement planning, inventory management, labour requirements, which ultimately result in loss of revenue. This paper deals with the key supply chain activities like planning, sourcing, making, deliver, coordination in the supply chain, information system and understanding the customers. Data is collected by administering a checklist and a percentage analysis is done to calculate the effectiveness of supply chain. Further the feasibility of implementing JIT practices is also analysed.